PENGGUNAAN VAKSIN Aeromonas hydrophila: PENGARUHNYATERHADAP SIANTAN DAN IMUNITAS LARVA IKAN PATIN (Pangasionodon hypophthalmus) - Lusiastuti, Angela Mariana; Hadie, Wartono (BERITA BIOLOGI, 2010)
Aeromonas hydrophila is a pathogen that often causes considerable losses in the area of freshwater fish fanning. Vaccination is one way to simulate parent catfish make specific immunity. Specific immunity generated by the parent will be forwarded through the oocytes produced during a certain time span. The aim of this research was to know the effect and the effectivity of using hydrovac vaccine with and without the complete adjuvant. This research was done on Patin fish Pangasionodon hypophthalmus whose givng Hydrovac 0.4 ml/kg of body weight. The comparation between complete adjuvant and vaccine was 1:1. Injection was done by intra peritoneal for three mothers each with and without complete adjuvant. Injection was done at gonad maturity level II. The result showed that antibody were positively detected on mother serum which used adjuvant or not. On larva stage, antibody was detected until four weeks old. While on 2 weeks old of larva, the concentration of titer antibody was very high and raised the dilution of 1: 2048. Survival rate of juvenile which their mother got a vaccine raised 93%, was better than 73%-63% using mother without vaccine. Booster immersion of hydrovac vaccine could give preferably at the end of three weeks old or in the beginning of fourth weeks old of larva.